(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines the challenges posed by information threats among university students, focusing on how best to develop, refine, and implement countermeasures. By analyzing foreign experience and emphasizing interdisciplinary strategies, the paper highlights the importance of media literacy, critical thinking, and collaborative international efforts. Recent scholarship and case studies from various countries reveal how malicious or manipulative information campaigns can undermine students’ academic performance and psychological well-being. Recommendations provided in this study draw upon established theoretical frameworks, while also proposing educational initiatives and policy measures designed to bolster students’ resilience in the modern, digitally integrated world.